2019
DOI: 10.1007/s11739-019-02253-7
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal anti-VEGF agents and cardiovascular risk

Abstract: Antagonists of Vascular Endothelial Growth Factor (Anti-VEGF) are widely administered by intravitreal injection for the treatment of ocular pathologies such as Age-related Macular Degeneration, Diabetic Macular Edema, Proliferative Diabetic Retinopathy and occlusion of retinal vessels. Anti-VEGF agents, in particular bevacizumab, were introduced in oncology to inhibit tumor-induced angiogenesis feeding neoplastic tissues. Subsequently, other specific agents were developed for intraocular administration.Whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 81 publications
0
56
0
1
Order By: Relevance
“…However, these treatments are not effective for every patient and they are associated with risks of complications. In particular, anti-VEGF agents have been linked to adverse effects on the photoreceptors and choroidal vessels as well as on the kidney and cardiovascular system [11][12][13]. Moreover, none of these treatments addresses neuronal damage or promotes tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…However, these treatments are not effective for every patient and they are associated with risks of complications. In particular, anti-VEGF agents have been linked to adverse effects on the photoreceptors and choroidal vessels as well as on the kidney and cardiovascular system [11][12][13]. Moreover, none of these treatments addresses neuronal damage or promotes tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…sVEGFR‐2, an endogenous soluble isoform of the VEGF‐C receptor, was reported to function as a specific inhibitor of lymphatic vessel growth, 46 a subsequent study revealed that sVEGFR‐2 suppressed tumor growth and lymph node metastasis in a mouse mammary model specifically through inhibition of lymphangiogenesis by sequestering VEGF‐C, while it did not affect angiogenesis 26 . As VEGF‐A maintains blood vessel integrity, prolonged systemic administration of anti‐VEGF‐A agents in cancer is accompanied by side‐effects (due to lack of normal VEGF functioning) such as increased risk of arterial hypertension and embolism 47 . It influences the survival of blood vessels in healthy tissues 48 as well.…”
Section: Discussionmentioning
confidence: 99%
“…26 As VEGF-A maintains blood vessel integrity, prolonged systemic administration of anti-VEGF-A agents in cancer is accompanied by side-effects (due to lack of normal VEGF functioning) such as increased risk of arterial hypertension and embolism. 47 It influences the survival of blood vessels in healthy tissues 48 as well. Therefore, sVEGFR-3 therapy may prevent side-effects through anti-angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-VEGF treatment necessitates several monthly injections to achieve desirable results during treatment of DME and causes treatment burden both financially and related to patient attendance [ 16 ]. Moreover, every injection may carry some risks such as endophthalmitis, cerebrovascular accidents even if they are seen very rarely [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%